Purpose and functions of legal responsibility - V. V. Sorokin (Правоприменение, 2018)
The subject. The article is devoted to the justification of the purpose and functions of legal responsibility, based on its essence as a method of training internal regulators of people’s behavior.The purpose of the article is to reconsider stereotypical notions of legal responsibility as a means of intimidation, of its purpose and functions.The description of methodology. The author uses methods of complex analysis, synthesis, as well as formal-legal, comparative-legal, research methods in combination with the spiritual and moral approach.The main results and scope of their application. The purpose of legal responsibility is to correct the lifestyle of an offender. A corrected way of life truly prevents the commission of new crimes. The function of deterrence is not absorbed by the warning function and can be considered as independent, since the entire procedural aspects of legal liability are riddled with fear and traumatic impact on the offender.Dehumanization is a common phenomenon in the legal relationship of legal responsibility, which is characterized by the emergence of prejudice, aggression, discrimination and racism. The law enforcement system should not deal with the dishumanization of people who stumbled, it should strengthen their human form and dignity, correcting their way of life. It is useless to frighten and punish, it is necessary to consider legal responsibility as a method of training the internal regulators of behavior in a person.Conclusions. While it is important for the state to fulfil the function of deterrence of criminals, the moral training function of legal responsibility is much more important for civil society. Only the corrected way of life really prevents the commission of new crimes. Goals and functions of legal responsibility should be formulated according to this conceptual idea.